2008
DOI: 10.1590/s0034-89102008000400025
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e validação de questionário multidimensional para medir não-adesão ao tratamento com medicamentos

Abstract: The study aimed to develop and validate an instrument capable of measuring non-adherence to drug treatment in its multiple dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
19

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 6 publications
(17 reference statements)
3
31
0
19
Order By: Relevance
“…Márquez Contreras et al 11 warned that questionnaires have low negative predictive value, confi rmed by the fact that 43% of users with uncontrolled high blood pressure reported that they were correctly following their treatment. Another important factor is reported by Santa Helena et al, 16 and refers to the conditions in which the questionnaire is carried out, dealing with undesirable behavior, which may intimidate the interviewees. In such cases, the method of completing the questionnaire may lead to adherence being overestimated, especially when it is completed by an interviewer, as patients tend to optimize their adherence in their responses, seeking the interviewers approval.…”
Section: Discussionmentioning
confidence: 99%
“…Márquez Contreras et al 11 warned that questionnaires have low negative predictive value, confi rmed by the fact that 43% of users with uncontrolled high blood pressure reported that they were correctly following their treatment. Another important factor is reported by Santa Helena et al, 16 and refers to the conditions in which the questionnaire is carried out, dealing with undesirable behavior, which may intimidate the interviewees. In such cases, the method of completing the questionnaire may lead to adherence being overestimated, especially when it is completed by an interviewer, as patients tend to optimize their adherence in their responses, seeking the interviewers approval.…”
Section: Discussionmentioning
confidence: 99%
“…O desenvolvimento e validação de questionários para avaliar a adesão ao tratamento foi objeto de dois estudos (6,18) . O Questionário MBG (Martín-Bayarre-Grau), desenvolvido na Escola Nacional de Saúde Pública de Cuba, foi elaborado a partir da definição de adesão terapêutica, desenvolvida pelos autores: ação ativa e voluntária do usuário a adotar um comportamento relacionado com o cumprimento do tratamento acertado de mútuo acordo com o seu médico (18) .…”
Section: Rev Esc Enfermunclassified
“…O questionário apresentou uma consistência interna Alfa de Cronbach de 0,889 e a validação de conteúdo foi realizada por experts (18) . elaborado para abordar o ato (se o indivíduo toma e o quanto toma de seus medicamentos), o processo (como ele toma o medicamento no período de sete dias, se pula doses, se toma de modo errático, se faz feriados) e o resultado de aderir (no caso, se sua pressão estava controlada) junto a usuários com AIDS em tratamento antirretroviral (6) .…”
Section: Rev Esc Enfermunclassified
See 2 more Smart Citations